Методи застосування просторово-часового доступу (SDMA) у системах мобільного зв’язку 5G - Літвінов, І. О.; Літвінов, О. О. (ХНУРЕ, 2023)
The object of the study is the process of applying the scheme of spatio-temporal access of mobile subscribers to base station resources in the 5G mobile communication system based on the use of an antenna array and methods of determining the direction of arrival of subscriber station call signals.The subject of research is models and methods of active use of space-time physical resources in 5G mobile communication systems. The purpose of the qualification work is to develop questions regarding the application of the multiple space-time access scheme in 5G mobile communication systems based on the use of methods of adaptive space-time processing of antenna array signals.
Keywords: SDMA; 5G